Implementation of Integrated Antenatal Care for Early Detection of Pregnancy Complications (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background: Antenatal care (ANC) is a vital healthcare service provided by trained medical professionals to monitor and support pregnant women from early gestation until childbirth. Comprehensive and routine ANC allows for the timely identification of abnormalities and potential risks during pregnancy, enabling healthcare providers to implement early and effective interventions that can prevent complications. Objective: This study aimed to examine the correlation between the implementation of integrated antenatal care and the early detection of pregnancy complications. Method: A comparative research design with a quantitative approach was used. The study population included third-trimester pregnant women, and a total of 66 respondents were selected using purposive sampling. Data were gathered through observation sheets, and both univariate and bivariate analyses were conducted using the chi-square statistical test. Results: The analysis revealed a significant association between the quality of integrated antenatal care services and the early identification of complications during pregnancy, with a p-value of 0.001. Conclusion: The findings indicate a strong and statistically significant relationship between the implementation of integrated antenatal care and the early detection of pregnancy-related complications. This suggests that when antenatal care services are well-coordinated, systematic, and consistently provided, the likelihood of detecting maternal health risks at an early stage significantly increases. Strengthening the quality and integration of antenatal care services can thus play a crucial role in improving maternal and fetal outcomes. These results support the need for continuous efforts in enhancing antenatal care delivery systems, particularly in high-risk pregnancy populations, to minimize delays in diagnosis and to promote proactive health interventions throughout the prenatal period.